Improvement financial reporting transparency of aid distribution center for Covid-19 victims at the Cipta Solo Berbagi Foundation - Estetika Mutiaranisa Kurniawati; Djoko Suhardjanto; Setianingtyas Honggowati; Djuminah Djuminah; Jaka Winarna (Universitas Muhammadiyah Magelang, 2022)
The objective of this program is to equip participants with the information and abilities necessary to prepare financial reports in compliance with PSAK 45 for a non-profit organization, specifically the Cipta Solo Berbagi Foundation. It is intended that through participating in this community service, the community, as the largest contributor to foundation funds, will have a better understanding of how the funds are managed and so improve trust in the foundation's management. Training and mentoring are provided as part of this program. Participants were very enthusiastic in participating in this program, as evidenced by the many questions regarding the material delivered. They begin to grasp how to record and generate financial reports by using examples of simple transactions that are encountered by partners in the foundation's operational activities.